Nitrogen dynamics in tropical soils applied with liquid and granular urea fertilizers - Md Motasim, Ahmmed; Abd Wahid, Samsuri; Abdul Sukor, Arina Shairah; Mohd Amin, Adibah (MDPI, 2021)
The mineralization of urea fertilizer mostly regulates the nitrogen dynamics in the soil. A laboratory-scale study was conducted to compare the nitrogen dynamics in two tropical soil series incubated with either liquid urea (LU) or granular urea (GU) at 0, 300, 400 or 500 mg/kg of soil. The soils samples used in the experiment were the Bungor and Selangor soil series which have a sandy clay loam and clay texture, respectively. The NH4 + -N, NO3 −-N concentration in the soils were measured for four weeks to determine the urea-N mineralization while ten pore volumes of water were used for the NH4 + -N and NO3 −-N leaching loss. At the same application rate, higher NH4 + -N and NO3 −-N concentrations were recorded in the LU applied soils throughout the incubation period in case of N mineralization. Urea-N recovery was higher in GU than LU treated soils in the first two weeks while no urea-N was present in both GU and LU treated soils after the third week of incubation. The leaching of N (NH4 + -N and NO3 −-N) was higher in GU treated soils than that of LU and leaching was increased with increased application rate in both LU and GU in both soils. The NH4 + -N and NO3 −-N concentrations were higher in the Selangor soil whereas the total N leaching loss was higher in Bungor soil. The results suggest that the LU was a better N fertilizer source than GU for rapid mineralization, quicker N availability and lower N leaching loss.